2014
DOI: 10.1016/j.carbpol.2013.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharides synthesis by highly stable immobilized β-fructofuranosidase from Aspergillus aculeatus

Abstract: The enzymatic synthesis of fructooligosaccharides (FOS) was carried out using a partially purified β-fructofuranosidase from the commercial enzyme preparation Viscozyme L. Partial purification of β-fructofuranosidase from Viscozyme L was done by batch adsorption using ion-exchange resin DEAE-Sepharose, showing a 6-fold increase in specific activity. The biocatalyst was then covalently immobilized on glutaraldehyde-activated chitosan particles. Thermal stability of the biocatalyst was evaluated at 50 °C and 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 30 publications
3
30
0
3
Order By: Relevance
“…Microbial fructofuranosidases have been immobilized on traditional supports, including calcium alginate (13), alginate-silica matrix (14), and nylon (15), as well as on new materials such as nanoparticles (16). Fungal fructofuranosidases have been also immobilized on different cellulosic supports such as wheat straw, corncobs, coffee husks, cork oak, loofa sponge (4), as well as glutaraldehydeactivated chitosan (17), and WA-30 anion-exchange resin (18). Despite the use of the above-mentioned cellulosic supports to immobilize fructofuranosidase, the discovery of new cellulosic materials that can reduce the costs associated with enzymatic hydrolysis and consequently lower the cost of the end product would increase industrial usage.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial fructofuranosidases have been immobilized on traditional supports, including calcium alginate (13), alginate-silica matrix (14), and nylon (15), as well as on new materials such as nanoparticles (16). Fungal fructofuranosidases have been also immobilized on different cellulosic supports such as wheat straw, corncobs, coffee husks, cork oak, loofa sponge (4), as well as glutaraldehydeactivated chitosan (17), and WA-30 anion-exchange resin (18). Despite the use of the above-mentioned cellulosic supports to immobilize fructofuranosidase, the discovery of new cellulosic materials that can reduce the costs associated with enzymatic hydrolysis and consequently lower the cost of the end product would increase industrial usage.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible shortcoming is that, unlike most conventional heterogenous catalysts, the immobilized biocatalyst in many cases experiences a substantial loss in activity after a limited number of reuses, typically between 7 and 15 cycles of reuse . As a result of the technical and functional advantages of the immobilized over the free enzyme reported in literature, many authors have proposed that the industrial application of an immobilized β ‐fructofuranosidase in scFOS production may offer economic advantages over the free enzyme …”
Section: Introductionmentioning
confidence: 99%
“…Commercial preparations of enzymes from strains of Aspergillus aculeatus (Pectinex Ultra SP‐L and Viscozyme L) and Aspergillus niger (Rohapect CM), with high transfructosylating activity have been successfully used to synthesize FOS. Moreover, studies involving the production of FFases were already reported using Aspergillus japonicus , A. niger and other filamentous fungi, such as Penicillium oxalicum , Penicillium citreonigrum , Penicillium sizovae , and Cladosporium cladosporioides , the last two standing out in the production of neo‐FOS and the last one in that of FOS using seawater .…”
Section: Introductionmentioning
confidence: 99%